(3OjhGf GdCOHs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3bGd GSMGb Hf GHQGgje JhdGg Gddg HYUeJg CeG HYO aEf Gddg bOQ GdGTjGA HbOQJg aCeG GdReGf agh Ref GdYde hGdHjGf s
(3BNQgG (B:s
(3hefgG eG jchf HeYfi faSg ef ZjQ Cf jQGO Hg TF ef gPg GdeYGfi cbhdc LQHg hcdeg s
(3HChdg agQSJs
(3GdeNWhW YHGQI Yf bWYI Ch ChQGb ef GdeLdO GdChd ef OjhGf GdGOHs
(3cJH Ydi UaMI GdYfhGf Cf eGdcg hehbag eMeO MSjf GdcGTGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B775s
Keywords: (3GddZIs